A Phase 1 Randomized Trial of Specific Active α‐Synuclein Immunotherapies PD01A and PD03A in Multiple System Atrophy. Issue 11 (3rd September 2020) - Meissner, Wassilios G.; Traon, Anne Pavy‐Le; Foubert‐Samier, Alexandra; Galabova, Gergana; Galitzky, Monique; Kutzelnigg, Alexandra; Laurens, Brice; Lührs, Petra; Medori, Rossella; Péran, Patrice; Sabatini, Umberto; Vergnet, Sylvain; et al.
Abstract: Multiple system atrophy (MSA) is a rare and fatal neurodegenerative disease with limited symptomatic treatment options. Aggregation of α‐synuclein in oligodendrocytes is believed to be a central mechanism of the neurodegenerative process. PD01A and PD03A are 2 novel therapeutic vaccine candidates containing short peptides as antigenic moieties that are designed to induce a sustained antibody response, specifically targeting pathogenic assemblies of α‐synuclein. The objectives of the current study were to evaluate primarily the safety and tolerability of PD01A and PD03A in patients with early MSA. Thirty patients (11 women) were randomized to receive 5 subcutaneous injections of either PD01A (n = 12), PD03A (n = 12), or placebo (n = 6) in this patient‐ and examiner‐blinded, placebo‐controlled, 52‐week phase 1 clinical trial (ClinicalTrial.gov identifier: NCT02270489). Immunogenicity and clinical scores were assessed as secondary objectives. Twenty‐nine patients reported a total of 595 treatment‐emergent adverse events (mild or moderate, n = 555; severe, n = 40). Treatment‐related adverse events included 190 injection‐site reactions typically observed in vaccination trials with similar per‐subject incidence in the treatment groups over time. Sustained IgG titers were observed in the PD01A‐treated group, and 89% of treated patients developed a PD01‐specific antibody response after receiving all injections. Induced antibodies displayed clear reactivity to the α‐synuclein target epitope. Titers and antibody responder rate (58%) were lower in the PD03A‐treated group. In conclusion, both PD01A and PD03A were safe and well tolerated. PD01A triggered a rapid and long‐lasting antibody response that specifically targeted the α‐synuclein epitope. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.